2013
DOI: 10.1021/jf304946p
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Transit of Dietary Methylglyoxal

Abstract: Methylglyoxal (MGO) is responsible for the pronounced antibacterial activity of manuka honey, in which it may reach concentrations up to 800 mg/kg. As MGO formed in vivo is discussed to play a role in diabetic complications, the metabolic transit of dietary MGO was studied within a 3 day dietary recall with four healthy volunteers. Determination of MGO in 24 h urine was performed with GC-MS after derivatization with O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine, and D-lactate was quantified enzymatically. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 46 publications
(85 reference statements)
2
78
0
Order By: Relevance
“…The cause of dicarbonyl stress remains unclear. It is unlikely due to decreased dicarbonyl excretion as there is little in normal health [7], although it is linked to renal function as dicarbonyl stress was a developing feature of both experimental nephrectomy and ureteral ligation [34]. Decreased Glo1 expression by hypoxia and inflammation, hypoxiainduced increased anaerobic glycolysis and decreased disposal of triosephosphates by the reductive pentosephosphate pathway (enzymes of which are inhibited by uraemic toxins) leading to increased formation of MG are likely causes.…”
Section: Chronic Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The cause of dicarbonyl stress remains unclear. It is unlikely due to decreased dicarbonyl excretion as there is little in normal health [7], although it is linked to renal function as dicarbonyl stress was a developing feature of both experimental nephrectomy and ureteral ligation [34]. Decreased Glo1 expression by hypoxia and inflammation, hypoxiainduced increased anaerobic glycolysis and decreased disposal of triosephosphates by the reductive pentosephosphate pathway (enzymes of which are inhibited by uraemic toxins) leading to increased formation of MG are likely causes.…”
Section: Chronic Renal Diseasementioning
confidence: 99%
“…It may also arise from other metabolic pathways where triosephosphates are intermediates: gluconeogenesis, glyceroneogenesis and photosynthesis. Dicarbonyls in foodstuffs are completely or partly metabolised and/or react with proteins before absorption in the gastrointestinal tract and impose dicarbonyl stress mainly in the gastrointestinal lumen [7,8]. Glyoxal and MG are metabolised mainly by glyoxalase 1 (Glo1) of the glutathione (GSH)-dependent glyoxalase system, with minor metabolism by aldoketo reductases (AKRs) and aldehyde dehydrogenases (ADHs).…”
mentioning
confidence: 99%
“…Glyoxal and methylglyoxal are mainly metabolized by glyoxalase system, and also aldehyde reductase and aldehyde dehydrogenase systems involve in a lesser extent [46]. It has been shown that dietary methylglyoxal do not contribute to urinary excretion levels of methylglyoxal and its metabolite D-lactate [47]. In addition to that, methylglyoxal formation in vivo may account ca.…”
Section: Content Of α-Dicarbonyl Compounds and Their Correlation Withmentioning
confidence: 99%
“…Although MG is regarded as a potential source of protein dysfunction, principally via glycation, it is uncertain whether direct MG ingestion can result in its survival and transport across the gut wall in sufficient quantities to provoke dysfunction [74,75]. In contrast, however, other studies have shown that diets containing high levels of glycated proteins (produced by MG treatment) can not only suppress the lifespan-extending effects of dietary restriction in mice [76], but also deleteriously affect memory in older humans [77,78].…”
Section: Methylglyoxal and Pdmentioning
confidence: 99%
“…That dietary glycated proteins, but not, perhaps, free dietary MG [74,75], are reported to be deleterious, raises the controversial possibility that intact glycated proteins could bind to RAGEs present on cells of digestive tract, thereby traverse the gut wall, to enter the enteric nervous system and then transfer to the CNS [82,83]. Furthermore, it is known that certain misfolded proteins, such as α-synuclein, can undergo cell-to-cell tranmission, analogous to prion proteins [84,85,86].…”
Section: Methylglyoxal and Pdmentioning
confidence: 99%